Haemoglobin blocks von Willebrand factor proteolysis by ADAMTS-13: A mechanism associated with sickle cell disease - Zhou, Zhou; Han, Hyojeong; Cruz, Miguel A.; López, José A.; Dong, Jing-Fei; Guchhait, Prasenjit (Thrombosis and Haemostasis, 2009)
Vascular occlusion, thromboembolism and strokes are hallmark events in sickle cell disease (SCD). The von Willebrand factor (VWF), largest adhesive protein in circulation, has been implicated as major component in these processes. In SCD, a high level of extracellular haemoglobin (Hb) in plasma has been shown parallely associated with the disease pathogenesis. Investigating the effect of Hb we observed that purified Hb significantly inhibited the ADAMTS-13 cleavage of VWF under static and flow conditions. Hb bound potently to VWF specifically VWFA2 in a saturation-dependent manner with half-maximal binding 24 nM. Inversely, VWFA2 also bound potently to Hb and binding was inhibited by VP1 antibody, which binds to ADAMTS-13 cleavage site on VWF. Microscopic observation also shows that Hb bound specifically to endothelial VWF under flow. Furthermore, the Hb-bound VWF multimers were isolated from plasma. Though, Hb bound also to ADAMTS-13, it is the Hb binding to VWFA2 that prevented the substrate being cleaved by ADAMTS-13. In an observation in a small pool of patients with SCD, high Hb in plasma was inversely correlated with low proteolytic activity of ADAMTS-13. Thus, the observations suggest that the patients with SCD suffer from an acquired ADAMTS-13 deficiency primarily because Hb competitively bound and blocked the proteolysis of VWF, leading to the accumulation of ultra-large VWF multimers in circulation and on endothelium. Therefore, the Hb-VWF interaction may be considered as a therapeutic target for treating thrombotic and vaso-occlusive complications in patients with severe intravascular haemolysis such as those with SCD.
Keywords: Extracellular haemoglobin; von Willebrand factor; ADAMTS-13 activity; sickle cell disease